Chemically vaporized cobalt incorporated wurtzite as photoanodes for efficient photoelectrochemical water splitting. (October 2019) - Khan, Humaira Rashid; Aamir, Muhammad; Malik, Mohammad Azad; Tahir, Asif Ali; Akram, Bilal; Murtaza, Ghulam; Choudhary, Muhammad Aziz; Akhtar, Javeed
Abstract: The development of low-cost, durable and efficient photocatalyst for overall photoelectrochemical water splitting is in demand to overcome the renewable energy crises. Herein, we demonstrate the efficient photoelectrochemical water splitting by cobalt (Co) incorporated zinc oxide (Zn1-x Cox O) thin films deposited via aerosol assisted chemical vapour deposition (AACVD) technique. The as-deposited Co incorporated ZnO thin films were characterised by powdered X-ray diffraction (pXRD), scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDX), transmission electron microscopy (TEM), high resolution transmission electron microscopy (HRTEM) and ultra violet-visible spectroscopy (UV-Vis). These films with different concentration of cobalt were investigated for water splitting applications and the best results were achieved for the films with 15% Co incorporation. Graphical abstract: Image 1